Short Communication: Population structure and habitat characteristics of Goniothalamus macrophyllus in Bukit Pembarisan forest, West Java, Indonesia - ilham adhya; PUDJI WIDODO; CECEP KUSMANA; EMING SUDIANA; IMAM WIDHIONO; TOTO SUPARTONO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Adhya I, Widodo P, Kusmana C, Sudiana E, Widhiono I, Supartono T. 2020. Short Communication: Population structure and habitat characteristics of Goniothalamus macrophyllus in Bukit Pembarisan forest, West Java, Indonesia. Biodiversitas 21: 1130-1135. Goniothalamus macrophyllus (Blume) Hook.f. & Thomson is a forest species with important medicinal value and widely used by many local communities. Excessive harvesting of this species has led to population decline and may lead to extinction. The aims of this research was to investigate population structure, habitat characteristics and environmental factors affecting local densities of G. macrophyllus in Bukit Pembarisan forest, Kuningan District, West Java, Indonesia. Purposive sampling was conducted at 17 locations during November 2017 to March 2018. The result showed that the population structure in the study area was dominated by seedlings (95% of the total number of individuals), followed by saplings (4%) and poles (0.1%). Seedlings, saplings, and poles were found growing across a wide elevational range (432-1,273 m asl.), at temperatures of 19-25°C, relative humidity of 80-90%, and soil pH of 4.61-6.46. The multiple regression analysis showed that soil nitrogen and soil pH affected seedling density, whereas soil clay content affected pole density. Our findings indicate that G. macrophyllus preferred acidic soils with high nitrogen and high clay content. We therefore recommend that future conservation efforts include the maintenance of existing poles, a prohibition on bark harvesting, and encouraging use of the leaves, rather than bark, for medicinal applications among consumers of G. macrophyllus.